2019
DOI: 10.1182/bloodadvances.2019000931
|View full text |Cite
|
Sign up to set email alerts
|

2019 sickle cell disease guidelines by the American Society of Hematology: methodology, challenges, and innovations

Abstract: The American Society of Hematology (ASH) convened 5 guideline panels to develop clinical practice recommendations addressing 5 management areas of highest importance to individuals living with sickle cell disease: pain, cerebrovascular complications, pulmonary and kidney complications, transfusion, and hematopoietic stem cell transplant. Panels were multidisciplinary and consisted of patient representatives, content experts, and methodologists. The Mayo Clinic Evidence-Based Practice Center conducted systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…The results observed in this study are similar to those obtained in the small open‐labeled studies of sildenafil use in SCD‐PH 12,16 . Those studies demonstrated potential utility of sildenafil and served to lay a framework for the design of the multicenter randomized, placebo‐controlled Walk‐PHaSST study.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The results observed in this study are similar to those obtained in the small open‐labeled studies of sildenafil use in SCD‐PH 12,16 . Those studies demonstrated potential utility of sildenafil and served to lay a framework for the design of the multicenter randomized, placebo‐controlled Walk‐PHaSST study.…”
Section: Discussionsupporting
confidence: 81%
“…As a result of these factors, the prospective clinical investigation of vasodilators approved for precapillary PH (similar to WHO Group 1 PAH) in SCD have largely halted. Despite this classification re‐assignment, many PH centers treating patients with SCD continue to use PAH medications off‐label in those with RHC‐defined precapillary PH, given the limited therapeutic options available 16 . In our clinical experience, some patients have tolerated PDE5‐I long‐term despite warnings against use of this class of medications.…”
Section: Introductionmentioning
confidence: 99%
“…The final guidelines, including recommendations, were reviewed and approved by all members of the panel. The approach is described in detail in Murad et al 14…”
Section: • Alloimmunizationmentioning
confidence: 99%
“…The work of this panel was coordinated with that of 4 other guideline panels (addressing other aspects of SCD) by ASH and the Mayo Clinic Evidence-Based Practice Research Program (funded by ASH under a paid agreement). 14 Project oversight was provided by a coordination panel, which reported to the ASH Guideline Oversight Subcommittee. ASH vetted individuals and appointed them to the guideline panel.…”
Section: Methodsmentioning
confidence: 99%
“…The Mayo Program vetted and retained researchers to conduct systematic reviews of evidence and coordinate the guideline development process, including the use of the GRADE approach. 14 The members of the guideline panel and the Mayo Program team are listed in supplemental File 1.…”
Section: Methodsmentioning
confidence: 99%